2022
DOI: 10.3390/antibiotics11091166
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Regional Pro-Adrenomedullin as a Prognostic Factor for Severe COVID-19 ARDS

Abstract: Mid-regional proadrenomedullin (MR-proADM) protects against endothelial permeability and has been associated with prognosis in bacterial sepsis. As endothelial dysfunction is central in the pathophysiology of severe SARS-CoV-2 infection, we sought to evaluate MR-proADM both as a prognostic biomarker and as a marker of bacterial superinfection. Consecutive patients admitted to the ICU for severe SARS-CoV-2 pneumonia were prospectively included and serum was bio-banked on days 1, 3, and 7. MR-proADM levels were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…However, it is interesting to note that the increase persists in the following days in accordance with the evolution of the disease, underlying the additional value of this biomarker in predicting the patient's outcome. In line with the evidence of other recent studies, which also proposed the analysis of the trend over time of this marker in the course of sepsis (42), we highlighted how MR-proADM could play a role in monitoring the progression of the disease (8), as evidenced by the results obtained on days 3 and 7. This analysis appeared to be a peculiarity of great interest in this work since it could allow the overcoming of some limitations of the punctual evaluations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is interesting to note that the increase persists in the following days in accordance with the evolution of the disease, underlying the additional value of this biomarker in predicting the patient's outcome. In line with the evidence of other recent studies, which also proposed the analysis of the trend over time of this marker in the course of sepsis (42), we highlighted how MR-proADM could play a role in monitoring the progression of the disease (8), as evidenced by the results obtained on days 3 and 7. This analysis appeared to be a peculiarity of great interest in this work since it could allow the overcoming of some limitations of the punctual evaluations.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding COVID-19-related severe acute respiratory syndrome (SARS-CoV2), an association between MR-proADM levels and virus-induced endothelial damage is assumed, as endotheliitis has emerged as a prominent feature of the severe COVID-19 disease (7). MR-proADM levels seem to reflect disease progression, allowing the identification of patients who are at the most risk of developing a more severe form of the disease (8). It could even be able to predict SARS-CoV2-induced mortality, although the pathological mechanism underlying this correlation has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen studies were included in the meta-analysis, with a total of 2,384 patients. Of the above studies, ten are prospective observational studies [ 37 , 38 , 41–44 , 46–49 ], and four are retrospective observational studies [ 36 , 39 , 40 , 45 ]. Five of them were conducted in Italy [ 36 , 39–41 , 47 ], two in Spain [ 37 , 42 ], two in Russia [ 44 , 49 ], one in Switzerland [ 38 ], one in the Netherlands [ 43 ], one in USA [ 45 ], one in France [ 46 ] and one in United Kingdom [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Spoto et al demonstrated a significant correlation between serum levels of PCT and MR pro-ADM in risk stratification of patients with pneumonia, while Önal et al evaluated the impact of MR pro-ADM and its prognostic role in sepsis and septic shock [ 35 , 37 ]. Other recent studies evaluated the prognostic value of the biomarker in patients with ARDS or pneumonia, with MR pro-ADM levels being useful for stratifying mortality risk and evaluating other forms of organ failure that can occur [ 38 , 39 ].…”
Section: Relevant Sectionsmentioning
confidence: 99%